A retrograde adeno-associated virus for collecting ribosome-bound mRNA from anatomically defined projection neurons - Cook-Snyder, Denise R.; Jones, Alexander; Reijmers, Leon G. (Frontiers in Molecular Neuroscience, 2015)
The brain contains a large variety of projection neurons with different functional properties. The functional properties of projection neurons arise from their connectivity with other neurons and their molecular composition. We describe a novel tool for obtaining the gene expression profiles of projection neurons that are anatomically defined by the location of their soma and axon terminals. Our tool utilizes adeno-associated virus serotype 9 (AAV9), which we found to retrogradely transduce projection neurons after injection at the site of the axon terminals. We used AAV9 to express EGFP-tagged ribosomal protein L10a (EGFP-L10a), which enables the immunoprecipitation of EGFP-tagged ribosomes and associated mRNA with a method known as Translating Ribosome Affinity Purification (TRAP). To achieve high expression of the EGFP-L10a protein in projection neurons, we placed its expression under control of a 1.3 kb Camk2a promoter. We injected the AAV9-Camk2a-TRAP virus in either the hippocampus or the bed nucleus of the stria terminalis (BNST) of the mouse brain. In both brain regions the 1.3 kb Camk2a promoter did not confer complete cell-type specificity around the site of injection, as EGFP-L10a expression was observed in Camk2a-expressing neurons as well as in neuronal and non-neuronal cells that did not express Camk2a. In contrast, cell-type specific expression was observed in Camk2a-positive projection neurons that were retrogradely transduced by AAV9-Camk2a-TRAP. Injection of AAV9-Camk2a-TRAP into the BNST enabled the use of TRAP to collect ribosome-bound mRNA from basal amygdala projection neurons that innervate the BNST. AAV9-Camk2a-TRAP provides a single-virus system that can be used for the molecular profiling of anatomically defined projection neurons in mice and other mammalian model organisms. In addition, AAV9-Camk2a-TRAP may enable the discovery of protein synthesis events that support information storage in projection neurons.